Effect of progesterone concentration on hCG trigger day on clinical outcomes after high-quality single blastocyst transfer in GnRH antagonist cycles - Jia, Nan; Xu, Jianing; Song, Bingbing; Hao, Haoying; Li, Meng; Zhang, Cuilian; Zhang, Shaodi (Frontiers in Medicine, 2024)
Abstract: Objective: To investigate whether progesterone levels on the human chorionic gonadotropin (hCG) trigger day are associated with clinical outcomes in fresh cycles and the first frozen-thawed cycles (the freeze-all strategy) following the transfer of a high-quality single blastocyst. Methods: This single-center retrospective analysis was conducted on patients undergoing in vitro fertilization with the gonadotropin-releasing hormone (GnRH) antagonist protocol from January 2017 to December 2023. The study included the first and second oocyte retrieval cycles with progesterone levels ≤2 ng/ml on hCG trigger day. Clinical pregnancy rates and early miscarriage rates were compared among groups using curve fitting, threshold effect analysis, and multivariable regression. Results: When progesterone levels were between 1-2 ng/ml, the pregnancy rate in fresh cycles was only 51% of that in cycles with progesterone levels ≤1 ng/ml (95% CI: 0.33, 0.79, P=0.0028). And the pregnancy rate decreased by 25% (95% CI: 0.51, 1.09) for frozen cycles, although there was no statistically significant (P=0.1273). When cycle types were used as a binary variable in multivariate regression analysis, it was found that the clinical pregnancy rate in frozen cycles was 1.84 times higher than in fresh cycles (OR=1.84, 95% CI: 1.38-2.47). For progesterone levels between 1-2 ng/ml, the clinical pregnancy rate in frozen cycles was 2.90 times that of fresh cycles (OR=2.90, 95% CI: 1.59, 5.29, P=0.0015). Progesterone levels on hCG day had no impact on the clinical pregnancy rate in thaw cycles, nor did they affect miscarriage rates in fresh or thaw cycles (P > 0.05). Conclusion: When progesterone levels on hCG trigger day were between 1-2 ng/ml, the clinical pregnancy rate for frozen-thawed cycles of high-quality single blastocyst transfer using an GnRH antagonist protocol significantly surpasses that of fresh cycles, thus elective frozen embryo transfer after the freeze-all strategy is recommended.